2005
DOI: 10.1128/jvi.79.18.12117-12121.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sustained CD8 + T-Cell Responses Induced after Acute Parvovirus B19 Infection in Humans

Abstract: Murine models have suggested that CD8؉ T-cell responses peak early in acute viral infections and are not sustained, but no evidence for humans has been available. To address this, we longitudinally analyzed the CD8 ؉ T-cell response to human parvovirus B19 in acutely infected individuals. We observed striking CD8 ؉ T-cell responses, which were sustained or even increased over many months after the resolution of acute disease, indicating that CD8 ؉ T cells may play a prominent role in the control of parvovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
5
31
0
3
Order By: Relevance
“…The kinetics of these memory cells are reminiscent of those observed in cytomegalovirus (CMV) infection, sometimes described as memory inflation, which is also seen in parvovirus B19 infection (20)(21)(22)(23). T cell responses to both PARV4 and B19 are persistent over the years, and this finding is consistent with our previous data on a cohort of chronically HCVinfected subjects in whom PARV4 T cell responses were detected decades after the primary infection (13,24). It was previously reported that up to 4.5% of CD8 ϩ T cells responded to a specific parvovirus B19 epitope (20), while PARV4 RMTENIVEV epitope-specific T cells represented 0.1 to 1.5% of the CD8 ϩ T cells in two individuals, at levels similar to those seen for CMV or other persistent infections (25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 92%
“…The kinetics of these memory cells are reminiscent of those observed in cytomegalovirus (CMV) infection, sometimes described as memory inflation, which is also seen in parvovirus B19 infection (20)(21)(22)(23). T cell responses to both PARV4 and B19 are persistent over the years, and this finding is consistent with our previous data on a cohort of chronically HCVinfected subjects in whom PARV4 T cell responses were detected decades after the primary infection (13,24). It was previously reported that up to 4.5% of CD8 ϩ T cells responded to a specific parvovirus B19 epitope (20), while PARV4 RMTENIVEV epitope-specific T cells represented 0.1 to 1.5% of the CD8 ϩ T cells in two individuals, at levels similar to those seen for CMV or other persistent infections (25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 92%
“…Longitudinal studies akin to the mouse models have been somewhat hard to establish in CMV, but parvoviruses B1936, 37 and more recently PARV438, 39 can be tracked following acute infection in adults and responses to specific epitopes show similar features of delayed expansion associated with maintained effector‐memory phenotypes and sustained functionality. Parvoviruses, such as these, do not undergo a latency programme, but can establish a long‐term DNA pool in tissues, and—if the T cells are to be trusted—these data indicate long‐term epitope production.…”
Section: What Is Memory Inflation Now?mentioning
confidence: 99%
“…Broad CD8+ T-cell responses to these epitopes were observed in acutely infected individuals and maintained or even increased over many months after the resolution of acute disease. Then, CD8+ T cells appear to play a prominent role in the control of B19V infection [274]. A discrepancy was observed in persistently infected individuals, where a comparatively higher reactivity was observed against viral capsid protein epitopes [275].…”
Section: Adaptive Immunity Cellular T-cell-mediated Immunementioning
confidence: 99%